ANALISIS TAFSIR TEMATIK AYAT-AYAT AL-QUR`AN TENTANG PENYIMPANGAN DALAM AGAMA ISLAM DI AKHIR ZAMAN - Fajar Zulkarnain Siregar; Siti Nurfara Adila; Mhd. Haris Pulungan; Nurunnisa Aini; Sartika (Al-Muhajirin: Jurnal Pendidikan Islam, 2024)
This study focuses on the contribution of religious fatwa MUI on the situation of religious life are colored by various types of discrimination, intolerance, and even violence based on religion. This study found that religious fatwas of the MUI, in practice it is used as a foothold by state officials to violate the freedom of religion/belief. Riskly, legal policy is no longer based on the constitution and the law, but the MUI fatwa. These conditions have spawned authoritarian government legitimized by religious views. On the other hand the fatwa provide religious life situations are colored by different types of discrimination, intolerance, and even violence based on religion. Problems of sexual deviation (lesbian, gay, bisexual and transgender) is currently a hotly debated topic society, starting from print and electronic media, from circles Islamic figures themselves allow gays and lesbians, on grounds that there is no difference between gay and non-homo and there is none the difference between lesbian and non-lesbian. According to them that Humans can only compete to do good deeds according to orders Lord. Islam teaches that a person is gay or lesbi like other humans, has the potential to become someone who pious or devout as long as he upholds religious values, ie not double-crossing God (shirk), believing in the apostleship of Muhammad SAW and carry out the worship that is commanded. He didn't hurt partner and do good to fellow human beings, to each other creatures and care for their environment.